2020
DOI: 10.1186/s12882-020-02126-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic kidney disease and risk factors in North-Central Nigeria: a population-based survey

Abstract: Background Chronic kidney disease (CKD) is a growing challenge in low- and middle-income countries, particularly in sub-Saharan Africa. There is insufficient population-based data on CKD in Nigeria that is required to estimate its true burden, and to design prevention and management strategies. The study aims to determine the prevalence of CKD and its risk factors in Nigeria. Methods We studied 8 urban communities in Kwara State, North-Central zone of Nigeria. Blood pressure, fasting blood sugar, urinalysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Variation in the parameters used to define obesity further compounds the difficulty in drawing robust conclusions. In a Nigerian community study including around 1,500 participants, Olanrewaju et al 54 found that obesity defined using the waist-to-hip ratio, not waist circumference or BMI, was associated with CKD (odds ratio, 1.5; 95% confidence interval, 1.10-2.05) ( Table 1 ). 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 In a cross-sectional study among teachers in South Africa, waist circumference was significantly associated with CKD, and in Senegal, a higher BMI was associated with CKD.…”
Section: Obesity and Ckd In Sub-saharan Africa: Choice Between Waist ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in the parameters used to define obesity further compounds the difficulty in drawing robust conclusions. In a Nigerian community study including around 1,500 participants, Olanrewaju et al 54 found that obesity defined using the waist-to-hip ratio, not waist circumference or BMI, was associated with CKD (odds ratio, 1.5; 95% confidence interval, 1.10-2.05) ( Table 1 ). 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 In a cross-sectional study among teachers in South Africa, waist circumference was significantly associated with CKD, and in Senegal, a higher BMI was associated with CKD.…”
Section: Obesity and Ckd In Sub-saharan Africa: Choice Between Waist ...mentioning
confidence: 99%
“…In a Nigerian community study including around 1,500 participants, Olanrewaju et al 54 found that obesity defined using the waist-to-hip ratio, not waist circumference or BMI, was associated with CKD (odds ratio, 1.5; 95% confidence interval, 1.10-2.05) ( Table 1 ). 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 In a cross-sectional study among teachers in South Africa, waist circumference was significantly associated with CKD, and in Senegal, a higher BMI was associated with CKD. 55 , 56 When participants with CKD were compared with those without CKD in a cross-sectional study from the Cape Town Vascular and Metabolic Health study, a significantly higher BMI (30.4 vs 28.2 kg/m 2 ), waist circumference (99 vs 90.8 cm), and visceral adipose tissue (228.4 vs 174.9 cm 2 ) were reported, but there was no significant difference in subcutaneous adipose tissue.…”
Section: Obesity and Ckd In Sub-saharan Africa: Choice Between Waist ...mentioning
confidence: 99%
“…Other studies done in Nigeria reported high prevalence of hypertension among their study participants [16,[33][34][35].…”
Section: Discussionmentioning
confidence: 74%
“…12 CKD is a growing challenge in low-and middle-income countries in Sub-Saharan African with 16% recorded as pooled prevalence [14,15]. In Nigeria, the prevalence of CKD is 1.8% to 43.5% depending on the studied population [16].…”
Section: Introductionmentioning
confidence: 99%
“…While the global prevalence of CKD is reported to be 13.4% [ 4 ], it is said to have a 13.9% prevalence in Sub-Saharan Africa [ 5 , 6 ]. Another study reported a 16% pooled prevalence of CKD in West Africa [ 7 ], the highest in Africa. Numerous research works have specified that CKD is more prevalent in developing countries [ 8 ].…”
Section: Introductionmentioning
confidence: 99%